Peran Pendidikan Antikorupsi Dalam Mencegah Korupsi Sejak Dini Melalui Sosialisasi di SMP 4 Muhammadiyah Pekanbaru - Nurul Hafiza; Sari Rambah Andini; Ilham Hudi; Winda Andini; Shakila Putri; Abelia Ananda; Ersa Deltia; Hanisah Putri (Lembaga Pengembangan Kinerja Dosen, 2024)
With this service, students of SMP 4 Muhammadiyah Pekanbaru are educated about anti- corruption literacy. Corruption is an act carried out to gain profit in a bad way, such as bribing, extortion, gratification, and others. The implementation plan is carried out in three stages. In the preparation stage, SMP 4 Muhammadiyah Pekanbaru carries out licensing, coordination, and socialization. The second stage is implementation, which includes socialization and counseling. The third stage is evaluation and preparation of reports. The results of the service show that students of SMP 4 Muhammadiyah Pekanbaru have the ability to avoid corruption after learning about anti-corruption.